2009
DOI: 10.1111/j.1600-0501.2009.01721.x
|View full text |Cite
|
Sign up to set email alerts
|

Transalveolar maxillary sinus floor elevation using osteotomes with or without grafting material. Part II: radiographic tissue remodeling

Abstract: When the transalveolar sinus floor elevation was performed without utilizing grafting material, only a moderate gain of new bone could be detected mesial and distal to the implants. On the other hand, when grafting material was used, a substantial gain of new bone was usually seen on the radiographs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
132
1
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(148 citation statements)
references
References 11 publications
13
132
1
2
Order By: Relevance
“…Consecuentemente, el anclaje óseo de los implantes dentales en la región posterior de la maxila puede mejorar significativamente mediante la creación de un espacio entre la membrana de Schneider y el piso del seno maxilar, proporcionando así el andamio necesario para la regeneración ósea en esta región (7,8).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Consecuentemente, el anclaje óseo de los implantes dentales en la región posterior de la maxila puede mejorar significativamente mediante la creación de un espacio entre la membrana de Schneider y el piso del seno maxilar, proporcionando así el andamio necesario para la regeneración ósea en esta región (7,8).…”
Section: Discussionunclassified
“…Cuando éstos implantes penetran 5mm dentro del seno maxilar, sólo se observa un crecimiento parcial de nuevo hueso hacia los ápices de los implantes. Por lo tanto, la necesidad de aplicar injertos óseos bajo la membrana sinusal para la elevación del piso del seno maxilar sigue siendo polémica (7,9).…”
Section: Discussionunclassified
“…1 The lateral window approach allows significant bone volume augmentation, regardless of maxillary sinus anatomical traits; whereas the transalveolar technique allows bone gain limited to 2 to 3 mm. 23 A systematic literature review concluded that implant survival rates after transalveolar sinus lift technique are drastically lower when initial bone height is less than or equal to 5 mm. 24 Moreover, this technique should be restricted to cases of nearly horizontal maxillary sinus floor.…”
Section: Discussionmentioning
confidence: 99%
“…Scientific evidence clearly indicates that using graft biomaterial in association with tSFE can effectively sustain bone regeneration. [19][20][21][22][23][24]. According to a systematic review, the incidence of membrane perforation following tSFE procedure ranges from 0 percent to 21.4 percent, and postoperative infection ranges from 0 percent to 2.5 percent.…”
Section: Transcrestal Approach (Tsfe)mentioning
confidence: 99%